Pendampingan Masyarakat pada Penyusunan Masterplan Ruang Publik di Perumahan Tulus Harapan Blok C Kota Semarang - Astari Wulandari; Ahmad Maulana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Along with the increase in population and the increasing need for facilities, vacant land in residential areas began to be looked at to be developed for meeting halls, communal parking spaces, commercial areas, playgrounds, and productive parks managed by residents. Related to these needs, to support community activities, it is necessary to have a master plan for public open space as a guideline for the use of space in the Tulus Harapan Blok C residence. If the existence of these facilities is not well organized, this residential area will experience a decrease in quality and community activities will not be well accommodated. Seeing this problem, it is necessary to have a guideline in the development of public open space in the Tulus Harapan Residence area in the form of a master plan. Thus, the master plan of public open space has a significant role as a tool for controlling space utilization and grouping facilities in the Tulus Harapan Housing Block C Residence. This community service activity is carried out as an effort to assist academics to housing residents in planning public spaces. The aim of this community service is to create a masterplan of public space development is prepared by the community simply through a mentoring process. This proves an increase in the ability of citizens to identify problems and formulate the needs for the development of public spaces systematically and structurally.